2006
DOI: 10.5194/angeo-24-3241-2006
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the impact of nonlinear interactions on the amplitude of the migrating semidiurnal tide

Abstract: Abstract. To quantitatively study the effects of nonlinear interactions on tide structure, a nonlinear numerical tidal model is developed, and the reliability and convergence of the adopted algorithm and coding are checked by numerical experiments. Under the same conditions as those employed by the GSWM-00 (Global Scale Wave Model 2000), our model provides the nonlinear quasi-steady solution of the migrating semidiurnal tide, which differs from the GSWM-00 result (the linear steady solution) in the MLT region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The former can be seen in a wider latitude range of 7.5°N–32.5°N, whereas the latter only appears at latitudes 0–12.5°N. Many numerical and observational studies (Huang et al ., ; ; ; ; ; ; ; ) suggested that an atmospheric wave with frequency f 3 could be excited by two prescribed waves (with different frequencies f 1 and f 2 , respectively) through interaction when their frequencies satisfy the matching conditions f 1 ± f 2 = f 3 . Barnett () and Mayr et al .…”
Section: Vertical Wave‐number Spectramentioning
confidence: 99%
“…The former can be seen in a wider latitude range of 7.5°N–32.5°N, whereas the latter only appears at latitudes 0–12.5°N. Many numerical and observational studies (Huang et al ., ; ; ; ; ; ; ; ) suggested that an atmospheric wave with frequency f 3 could be excited by two prescribed waves (with different frequencies f 1 and f 2 , respectively) through interaction when their frequencies satisfy the matching conditions f 1 ± f 2 = f 3 . Barnett () and Mayr et al .…”
Section: Vertical Wave‐number Spectramentioning
confidence: 99%
“…A detailed description of the computational method was presented by Huang et al (2006Huang et al ( , 2007. Considering the spatial scales of the initial GW, x and z are set to 10 and 0.4 km, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Gravity waves (GWs) play an important role in atmospheric dynamics and strongly influences the local and global atmospheric dynamical processes and atmospheric structures (Alexander, ; Alexander & Pfister, ; Fritts & Alexander, ; Fritts & Rastogi, ; Lindzen, ). Meanwhile, the GWs propagation will also be affected by the background atmosphere they propagate through (e.g., Heale & Snively, ; Huang et al, , , , ; Zhang & Yi, , ). Previous studies (e.g., Fritts & Yuan, ; Hecht et al, ; Vadas, ; Walterscheid et al, ; Walterscheid & Hickey, ) suggested that if the atmospheric temperature or wind satisfies the specific conditions, gravity wave (GW) ducting can occur.…”
Section: Introductionmentioning
confidence: 99%